Black and Green : Afro-Colombians, Development, and Nature in the Pacific Lowlands - Asher, Kiran (Book collections on Project MUSE., 2009)
Looks at development of Afro-Colombian communities after passage of a 1991 law granting cultural rights and collective land ownership to the communities, arguing that social movements are often partially co-opted by market or state, but then use state res